+0  
 
0
254
2
avatar+42 

x= -8/3 , 2(3x^2+24x+48)+1(x-6)=2(1)

 

IS THE ANSWER EQUAL??????!!

TO EACH OTHER?

Virax1o1  Jun 1, 2017
 #1
avatar+7155 
+2

If    \(x=\,-\,\frac83\)   , does    \(2(3x^2+24x+48)+1(x-6)=2(1)\)   ?

 

 

Replace every   " x "   with   \( -\,\frac83 \)   in the second equation.

 

\(2(3(-\frac83)^2+24(-\frac83)+48)+1((-\frac83)-6)\stackrel{?}{=}2(1) \\~\\ 2(3(\frac{64}{9})-64+48)+(-\frac{26}3)\stackrel{?}{=}2 \\~\\ 2(\frac{64}{3}-16)-\frac{26}3\stackrel{?}{=}2 \\~\\ 2(\frac{16}{3})-\frac{26}3\stackrel{?}{=}2 \\~\\ \frac{32}{3}-\frac{26}3\stackrel{?}{=}2 \\~\\ \frac63\stackrel{?}{=}2 \\~\\ 2=2\quad\text{ true!}\)

hectictar  Jun 1, 2017
 #2
avatar+42 
+1

Thank you very much!!

Virax1o1  Jun 1, 2017

5 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.